Efficiency of metaphase II oocytes following minimal/mild ovarian stimulation in vitro fertilization. Issue 1 (December 2016) - Zhang, John; Yang, Mingxue; Merhi, Zaher
Abstract Background An inverse relationship between oocyte efficiency and ovarian response was reported in conventional IVF. The purpose of this study was to report metaphase II (MII) oocyte efficiency according to oocyte yield in minimal/mild stimulation IVF (mIVF) and to assess whether oocyte yield affects live birth rate (LBR). Methods Infertile women (n  = 264) aged < 39 years old with normal ovarian reserve who had mIVF were recruited. All participants received the same protocol for ovarian stimulation. All the embryos were cultured to the blastocyst stage and vitrified using a freeze-all approach. This was followed by a single blastocyst transferred to each participant in subsequent cycles over a 6-month period. Ovarian response was categorized according to the number of MII oocyte yield (low: 1–2, intermediate: 3–6 and high ≥ 7 MII oocytes). MII oocyte utilization rate was calculated as the number of live births divided by the number of MII oocytes produced after only one oocyte retrieval and subsequent transfers of vitrified/warmed blastocysts. The main outcome measure was cumulative LBR over a 6-month period. Results Among all the participants, 1173 total retrieved oocytes (4.4 ± 0.2 per patient) resulted in 1019 (3.9 ± 0.2 per patient) total MII oocytes, a clinical pregnancy rate of 48.1 % and a LBR of 41.2 %. Oocyte utilization rate was inversely related to ovarian response where it was 30.3 % in the "low" vs. 9.3 % in the "intermediate" vs. 4.3 % in the "high" oocyte yield groups (p  < 0.05). Implantation rate significantly dropped as the number of MII oocytes increased and was highest in the "low" oocyte yield group (p  < 0.0001). Cumulative LBR was similar in "low, " "intermediate, " and "high" oocyte yield groups (p  > 0.05). The number of MII oocytes had poor sensitivity and specificity for predicting a live birth. Conclusion These data extend the hypothesis of oocyte efficiency reported in conventional IVF protocols to mIVF protocols. Trial registration Registration clinicaltrials.gov:NCT00799929 .